Urgensi Pendidikan Anak Usia Dini Di Era Digital: Tinjauan dalam Pendekatan Teoritis dan Aplikatif - Sumarno Sumarno (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
The Education is a process of change that is done consciously to make man better (change behavior). In the process of formal education in Indonesia there are several stages that must be traversed starting from early childhood education (OLD) up to the college level. Early childhood education is the initial capital for the sustainability of education at a later stage, since an early age at the child save a very powerful memory in the process of education. What is in this digital era ofearly childhood education on the need to gain serious attention. In this discussion of the methods used by the author is with the literature review with library research or study approach to librarianship. In the discussion it can be inferred that the urgency of early childhood education in the digital age this parents should do the action as follows; first, don't be familiarized and limit the use of Gadgets there are small. second, Encourage Children to do Motor activity. third, the selection of the Media or the right impressions and safe for children. fourth, Monitor the environment either in cyberspace or in the vicinity.Keywords: education, early childhood, digital